Investigating the influence of environmental information on perceived indoor environmental quality: An exploratory study. (1st May 2022) - Tang, Hao; Ding, Yong; Liu, Xue; Singer, Brett C.
Abstract: Under the assumption that information can impact perception, most research on human sensation and satisfaction with indoor environmental quality (IEQ) parameters has been conducted with respondents uninformed about the test conditions. Therefore, researchers know little about the impact of information on perception. These potential effects are increasingly relevant as quantitative information about indoor environments becomes accessible via low-cost, wirelessly connected sensors. In this experimental study, 48 subjects were exposed to varied indoor environmental conditions and provided with different types of environmental information. The subjects' sensation and satisfaction were compared when they were blinded or provided with quantitative information about and/or qualitative ratings of specific parameters. The results indicate that accurate information on parameter values influenced how the subjects perceived the indoor air quality (IAQ) but not how they perceived the thermal, acoustic, or visual quality. The subjects rated the IAQ more positively when they were informed that there were nonzero ventilation rates. The qualitative ratings influenced the subjects' perceptions of all four environmental factors, but in different directions. The subjects generally had more positive sensation and higher satisfaction when they were told that the parameter values and qualitative ratings were more favorable than the test conditions. However, the improved sensation and satisfaction were often not as good as when the environmental conditions were actually improved and the subjects were provided with accurate information. These findings affirm the critical need for more research on the impacts of information on perceptions of the indoor environment. Highlights: Subjects perceived better indoor air quality when they knew ventilation rate. Accurate values of temperature, sound and illuminance did not impact perceptions. Qualitative information had impact on perceptions of four environmental aspects. Subjects' perceptions can be misled by providing misleading information.